Oxford Research Encyclopedia of Neuroscience 2020
DOI: 10.1093/acrefore/9780190264086.013.50
|View full text |Cite
|
Sign up to set email alerts
|

Phantom Limbs and Brain Plasticity in Amputees

Abstract: Phantom sensations are experienced by almost every person who has lost their hand in adulthood. This mysterious phenomenon spans the full range of bodily sensations, including the sense of touch, temperature, movement, and even the sense of wetness. For a majority of upper-limb amputees, these sensations will also be at times unpleasant, painful, and for some even excruciating to the point of debilitating, causing a serious clinical problem, termed phantom limb pain (PLP). Considering the sensory organs (the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 132 publications
(134 reference statements)
0
4
0
Order By: Relevance
“…Following peripheral nerve injury or limb amputation, the primary sensory and motor cortices undergo remapping, where the affected regions have persistent but suppressed cortical representation (Makin et al, 2020; Wesselink et al, 2019). The extent of this cortical remapping correlates with the intensity of PLP, where more severe PLP results in more extensive remapping (Gunduz et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Following peripheral nerve injury or limb amputation, the primary sensory and motor cortices undergo remapping, where the affected regions have persistent but suppressed cortical representation (Makin et al, 2020; Wesselink et al, 2019). The extent of this cortical remapping correlates with the intensity of PLP, where more severe PLP results in more extensive remapping (Gunduz et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Several mechanisms have been proposed to explain cortical remapping, including axonal sprouting in the primary somatosensory cortex (Florence et al, 1998), thalamus, and brainstem (Jones and Pons, 1998), the expansion of the receptive field in the thalamus (Davis et al, 1998;Jain et al, 2008), unmasking or disinhibition of inhibitory connections between somatotopic regions (Li et al, 2014), or unmasking of overlapping receptive fields in the primary somatosensory cortex (Wesselink et al, 2022). Evidence to support the preservation, but suppression, of the canonical topographic cortical map following a limb amputation stems from studies where the nervous system was stimulated and sensory percepts were evoked (Makin et al, 2020). Sensory percepts have been evoked in the missing limbs of people with amputations using electrical stimulation of the peripheral nerves, (Anani and Körner, 1979;Charkhkar et al, 2018;Clippinger et al, 1982;D'Anna et al, 2017;Raspopovic et al, 2014), spinal cord (Chandrasekaran et al, 2020;Nanivadekar et al, 2022aNanivadekar et al, , 2022b, and thalamus (Davis et al, 1998), as well as magnetic stimulation of the contralateral primary motor cortex (Bestmann et al, 2006;Reilly and Sirigu, 2008).…”
Section: Plasticity In Sensorimotor Pathways Following Limb Amputationmentioning
confidence: 99%
“…This reported breathability problem is in accordance with previous observations made by several authors [6,47], who claimed that more attention must be paid by researchers, clinicians and manufacturers of prosthetic components to the heat-related biomechanics of soft tissues, a proper fabrication technique, better material selection and the introduction of efficient thermoregulatory systems [6]. Nevertheless, it must be taken into account that wetness may sometimes be altered by phantom pain, which has a high prevalence in adult upper limb amputees and implies sensations like an altered sense of touch, altered temperature and even the sense of wetness [48].…”
Section: Comfortmentioning
confidence: 99%
“…Studies of humans with prosthetic limbs have shown neural representations that are specific to their prosthetic rather than biological limb, as seen when the prosthetic differs from an actual limb in form (such as a hook for a hand) [97]. Studies of primate amputations have shown that the primary motor representation of body parts are plastic following finger amputations, as neural regions are redistributed to non-amputated fingers [98]. This neuroplasticity within neural regions has thus far limited rather than facilitated the advancement of neural bypasses.…”
Section: The Role Of Neuroplasticity As Hindrance or Helpmentioning
confidence: 99%